ANALYSIS OF STUDENTS' READING INTERESTS IN INTRA MADRASAH STUDENT ORGANIZATIONS AT MTS NEGERI 2 TRENGGALEK IN THE 2025/2026 ACADEMIC YEAR - Eva Zulvi Wityastuti; Kamas Tontowi (CV. Bunda Ratu, 2026)
Reading interest plays an important role in improving literacy skills and supporting students’ academic success. This study aimed to identify the level of reading interest among students involved in the Intra-Madrasah Student Organization (OSIM) at MTs Negeri 2 Trenggalek in the 2025/2026 academic year. A descriptive quantitative approach was employed, involving 40 OSIM members as participants. Data were collected through questionnaires and analyzed using descriptive statistics based on frequency and percentage. The findings indicated that most students demonstrated a fairly good level of reading interest. They enjoyed reading in various places, showed interest in knowledge-based books, and read not only for examinations but also to gain information and broaden their knowledge. Students’ reading interest was supported by the school environment, literacy culture, library facilities, and organizational activities. The study concludes that OSIM students possess a fairly good level of reading interest and literacy awareness, which should be strengthened through sustainable literacy programs.